A. Cavaco-Silva. Economic effects of public debt. Nueva York : Martin Robertson, 1977. 147 p. (York studies in economics) - Caso Raphael, Agustín (Estudios Demográficos y Urbanos, 1978)
A. Cavaco-Silva, Economic Effects of Public Debt, York Studies in Economics, Nueva York, Martin Robertson, Ed., 1977.